Pinch analysis based approach to safety risk management in the process industries - Tan, Raymond Girard R. (Animo Repository, 2015)
Pinch Analysis is an established method for enhancing the sustainability of industrial processes via efficient use of various resources. It is based on the principle of target identification followed by subsequent system design aided by a problem decomposition strategy using the Pinch Point. This approach has recently been extended to a broad range of structurally analogous problems in various domains, such as financial management, carbon-constrained energy planning, etc. In this work, a novel graphical methodology for risk management in the process industries is proposed. In this approach, it is assumed that there a set of risk reduction measures is available, and that each measure is characterized by its implementation cost and the degree of risk criticality that it addresses. These data are then used to generate a Source Composite Curve. Targeting can then be achieved by shifting this curve relative to a pre-defined Sink Composite Curve, which represents the locus of the plant management's "willingness to pay", or budget relative to risk criticality. The methodology is then demonstrated on a case study based on the well-known Bhopal incident. Copyright © 2015, AIDIC Servizi S.r.l.,.